Managerial economics markets and the firm - Boyes, William J. (South-Western/Cengage Learning, 2012)
This title examines organizational behavior, strategic management, human resource management, and emerging issues such as game theory, TQM, and information economics. It departs from convention to illustrate the role of economic intuition in making sound business decisions.